Community Economic Empowerment in the Ngoro Village PKK Group Through Orchid Cultivation - Utami, Budi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Orchids are a type of diverse and beautiful flower plant found throughout the world, including Indonesia. Orchids naturally thrive in forest environments or areas with abundant moisture and organic nutrients. Considering the decreasing area of forest, it is important to take immediate action to preserve and protect various orchid species that are threatened with extinction. The Ngoro Village PKK group together with Damar Farm held orchid planting training which highlighted the potential for cultivating quality orchid plants. The aim of this effort is to provide education to the local community and supervise orchid cultivation as a means of earning a living for the family. The approach taken is through practice and question and answer sessions. Participants included sub-district heads and women from the PKK group in Ngoro Village. This material provides an overview of orchids, including the characteristics, potential, and techniques for propagating and cultivating these plants. The results of these efforts resulted in a significant increase in participants' understanding of orchid plants. There are two types of orchids that are commonly used for training: pigeon orchids (Dendrobium crumenatum) and ground orchids (Spathoglottis plicata). This orchid is famous for its ease of reproduction by separating young plants. Coconut fiber is an orchid planting medium that is often found in this area.